The Effectiveness of the Reality Counseling Program in Improving the Self-Esteem of Adolescents from Divorced Families - Elshamy, Hany Ibrahim; Abdelrahman, Mohamed Kamal; Eliwa, Mahmoud Abdelaziz (Journal of Educational and Psychological Sciences, 2024)
Divorce of spouses disrupts the family foundation and can cause serious damage to children’s development and healthy personality. Consequently, the majority of these children need psychological rehabilitation programs. Aims. Investigating the effectiveness of a reality therapy program on improving the self-esteem of preparatory stage students from divorced families. Methods. The Experimental Method has been used, through which the researcher tries to reconstruct reality in an experimental situation to reveal the effect of an experimental variable (a reality therapy program) on a specific dependent variable (self-esteem) in conditions in which the researcher controls some other variables. Sample. The sample of the basic study in its entirety consisted of 30 students from the second year of middle school, who returned the forms of the two scales after filling them. Instruments. To collect and analyze data, self-esteem was used. Findings. The results indicated that there were statistically significant differences between the mean ranks of the experimental group (mean rank = 23) and the control group (mean rank = 8) on self-esteem variables in post-test and the differences were significant at the level (0.01) in favor of the experimental group. This program helps the children of divorced parents improve their self-esteem in a way that enables them to adapt to their social environment. Conclusion. The study concludes that the reality counseling program significantly improves the self-esteem of adolescents from divorced families. The experimental group’s substantial improvement over the control group underscores the program’s efficacy. These findings suggest that such psychological interventions can be vital in supporting the emotional and social adjustment of children from disrupted family backgrounds.